A wind tunnel rig to study the external fan cowl separation experienced by compact nacelles in windmilling scenarios - Sabnis, Kshitij; Babinsky, Holger; Boscagli, Luca; Swarthout, Avery E.; Tejero, Fernando; MacManus, David G.; Sheaf, Christopher T. (American Institute of Aeronautics and Astronautics (AIAA), 2023)
Ultra high-bypass ratio aircraft engines adopt slim fan cowl profiles which are sensitive to separation on their external surfaces under diversion windmilling conditions, when engine shutdown occurs during cruise. A two-dimensional wind tunnel rig is developed to investigate the separation mechanisms experienced by aero-engine nacelles in such scenarios to establish the detailed aerodynamics. The tunnel flow field with entry Mach number 0.65 broadly replicates the expected diversion windmilling flow behaviour for a full-scale nacelle, featuring a supersonic region which terminates in a normal shock wave on the external fan cowl surface. For the three conditions investigated, which relate to different engine mass-flow rates, the response of the boundary layer in this region progresses from remaining fully attached through to well-established separation. However, the rig Reynolds number based on nacelle lip thickness is about 1.2 million, roughly one-third of full scale, resulting in a transitional rather than turbulent shock-boundary-layer interaction. Nevertheless, simple simulations correctly predict the wind tunnel flow field, except for the precise boundary-layer response to normal shock waves, and so experimental data from the rig can be used to validate relevant computational methods.